Association of bacterial vaginosis with periodontitis in a cross-sectional American nationwide survey - Escalda, Cláudia (Sci Rep, 2021)
To explore the association between bacterial vaginosis (BV) and periodontitis (PD) and to determine whether PD and BV might be linked with systemic serum alterations. We used the National Health and Nutrition Examination Survey 2001–2004, with women aged 18–49 years old and diagnosed with or without BV according to Nugent’s method. PD was defined according to the 2012 case definition. We compared serum counts according to the presence of PD and the presence of BV. Multivariable regression was used to explore and identify relevant variables towards the presence of BV. 961 women fulfilled the inclusion criteria. In women with BV, PD was associated with higher inflammation, characterized by increased white blood cells (p = 0.006) and lymphocyte (p = 0.009) counts. Predictive models presented a statistically significant association between PD and BV [Odds Ratio (OD) = 1.69, 95% Confidence Interval (CI): 1.09–2.61 for periodontitis; OD = 2.37, 95% CI: 1.30–4.29 for severe PD]. Fully adjusted models for age, smoking, body mass index, diabetes mellitus and number of systemic conditions reinforced this association [OD = 1.71, 95% CI: 1.06–2.76 for PD; OD = 2.21, 95% CI: 1.15–4.25 for severe PD]. An association between BV and PD is conceivable. PD was associated with higher systemic markers of inflammation in women with BV. Our data is novel and could serve as a foundation to guide future studies in the confirmation of this association and the underlying mechanisms.